3D world : the international magazine for 3D artists. (Bath : Future)
3D World Magazine is the perfect subscription for anyone interested in 3D graphics and animation. It's packed with tutorials, interviews, and reviews of the latest 3D software and hardware. Whether you're a beginner or a professional, 3D World Magazine has something for everyone.
Keywords: Industrieel ontwerpen; Multimedia en communicatietechnologie